INDUKSI EMBRIOGENESIS MIKROSPORA Nicotiana tabacum L. cv. Vorstenlanden DENGAN STRES PANAS DAN PELAPARAN - Zuchrotus Salamah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
The aims of this research is to know the effect of heat shock 34oC and starvation of  the tobacco,  Nicotiana  tabacum  L.  cv. Vorstenlanden  microspore. Isolated  microspore subjected  to  stress  by  culturing  in  starvation  B medium  and incubated  at 34 oC for  7 days in  dark. After 7 days in  starvation  medium the  microspore  were  subcultured  to  theen-rbriogenesis  medium (A2  mediun-r),  incubated  in  dark  during  4 weeks at25u  C. Result slrowed that  late  uninucleat  microspore  was found  in  the  bud  with  flower  erown size (9-10) mm  with precentage  of 69%. After stres  cytoplasm  of  the  microspore nrorfologycally  change,  showed star like  (tipe-3)  21%  . Multicellular microspore  was for"rnd  in  the  embriogenesis  medium  at 4%  in  the  cv Vorstenlanden.